Anti-Transitional-Asynchrony Control for a Class of Hybrid Fuzzy Systems With Application to Bicopter - Yang, Jianan; Zhu, Yimin; Wu, Tong; Zhang, Lixian; Shi, Yang (IEEE transactions on fuzzy systems, 2023)
This article is concerned with a class of discrete-time hybrid fuzzy systems subject to semi-Markov switching, in which the sojourn time of each mode is with upper and lower bounds. A practical scenario of transitional asynchrony is taken into account for the first time, where the switchings of controllers to be designed lag behind the ones of the controlled plant, and the lags depend on the transition between adjacent modes. By means of the semi-Markov kernel approach, numerically testable stability criteria are obtained, based on which existence conditions of the anticipated stabilizing controller capable of overcoming the transitional asynchrony are derived. Compared with the previous studies assuming the mode-independent or mode-dependent lags, the derived results are less conservative. Two illustrative examples including a class of bicopters are given to demonstrate the effectiveness and potential of the designed anti-transitional-asynchrony controllers.